2022
DOI: 10.2478/jofnem-2022-0004
|View full text |Cite
|
Sign up to set email alerts
|

Description of Boleodorus bushehrensis n. sp. (Rhabditida: Tylenchidae) from Southern Iran, and Observations on a Commonly Known Species

Abstract: A new species of the genus Boleodorus, recovered from southern Iran, is described and illustrated based upon morphological and molecular data. B. bushehrensis n. sp. is mainly characterized by having a wide and low cephalic region (which is continuous with the adjacent body), the oral aperture in a depression in side view under a light microscope, four lines in the lateral field, weak metacorpus with a vestigial-to-invisible valve, and short (26–38 mm long) hooked tail with rounded tip. The females are 334–464… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Furthermore, the interpretation of morphological and morphometric differences as "intraspecies variations" may yield to incorrect assignments of given populations to species. In a study by Monemi et al (2022), it has been shown that several sequences assigned to Boleodorus thylactus Thorne, 1941 have occupied different placements in corresponding trees, and as the conclusion, the original descriptions of the Tylenchidae species or data given in redescriptions of the species based on type specimens, are reliable resources in taxonomic studies of this group of nematodes. In accordance with some recent phylogenies using ribosomal markers (e.g.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, the interpretation of morphological and morphometric differences as "intraspecies variations" may yield to incorrect assignments of given populations to species. In a study by Monemi et al (2022), it has been shown that several sequences assigned to Boleodorus thylactus Thorne, 1941 have occupied different placements in corresponding trees, and as the conclusion, the original descriptions of the Tylenchidae species or data given in redescriptions of the species based on type specimens, are reliable resources in taxonomic studies of this group of nematodes. In accordance with some recent phylogenies using ribosomal markers (e.g.…”
Section: Discussionmentioning
confidence: 98%
“…The new species has a low flat lip region, which has already been reported for some other Tylenchidae spp. (Geraert, 2009; Monemi et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The morphometrics of most species of Tylenchidae have been expanded following numerous reports ( Geraert, 2008 ); however, most of the original and subsequent reports lack molecular sequences, making the identification of most of the species questionable. Monemi et al (2022) stated that most of the sequences assigned to Boleodorus thylactus Thorne, 1941 probably belong to cryptic forms, and therefore, topotype sequences of the species are needed to decide on their identity. Likewise, topotype sequences have been used to prove the status of sequences assigned to Xiphinema brevicolle Lordello and Da Costa, 1961 ( Lazarova et al, 2019 ) and X. robbinsi Pedram, Niknam & Decraemer, 2008 ( Jahanshahi Afshar, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…was compared with other available sequences in the GenBank database using the basic local alignment search tool (BLAST). Relevant sequences (mostly belonging to the subfamily Tylenchinae) used in SSU phylogeny in previous studies ( Monemi et al, 2022 ) were selected for inferring the SSU tree. Two sequences of Aphelenchoidea Fuchs, 1937, namely Bursaphelenchus mucronatus Mamiya & Enda, 1979 (AY284648) and Aphelenchoides fragariae Ritzema Bos, 1890 (AY284645), were selected as outgroups.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation